TINGKAT KESESUAIAN KINERJA PELAYANAN KARGO PT ANGKASA PURA II (PERSERO) TERHADAP KEPENTINGAN MITRA USAHA - Aswanti Setyawati; Jafar Shaddiq Assegaf (Institut Transportasi dan Logistik Trisakti, 2015)
The object of this study aimed to analyze the satisfaction of the expectations/ interests of business partners in the Cargo Terminal of Soekarno Hatta Airport in Semester 1 2014, with a population of 36 Business Partners. Through quantitative and qualitative methods with the Likert scale is used to find the level of suitability and Cartesian diagram, as well as methods Customer Satisfaction Index, appears clearly how the average value of the variable X or business partner satisfaction was 3.75. Meanwhile, the average value of the variable Y or expectations/ interests of business partners were 4.25. Meanwhile, the level of concordance between the variables X and Y variables amounted to 88.35%. This means not yet reached the optimum level of satisfaction, in actual, what is expected of business partners still needs special attention from the company. In a Cartesian diagram there is only one factor that goes in quadrant A is a factor of 2. In diagram B, there are five factors that go in it is a factor of 1, 3, 4, 8 and 9 — In quadrant C, there are two factors, namely factor 6 and 7, were entering the quadrant D is a factor of 10 and 5. Customer Satisfaction Index scores conclude that the figures obtained Customer Satisfaction Index is 0.74, meaning that, although not yet reached a maximum, however, there is already a pretty good satisfaction felt by the business partner.